International experience with minocycline, EDTA and ethanol lock for salvaging of central line associated bloodstream infections. (3rd June 2018) - Hachem, Ray; Kanj, Souha; Hamerschlak, Nelson; Saad, Hala; Assir, Fernanda Ferraz; Mori, Nobuyoshi; Jiang, Ying; Ghaly, Fady; Chaftari, Anne Marie; Raad, Issam I
ABSTRACT: Background : The use of long-term central venous catheters (CVCs) could lead to serious bloodstream infections. Removal of the infected CVC and reinsertion of a new CVC are not always feasible and alternative lock therapy may be considered. We conducted a multicenter trial to assess the efficacy and safety of the lock therapy. Methods : Between October 2013 and August 2014, we prospectively enrolled 20 patients with catheter-related bloodstream infections (CRBSIs) or central line-associated bloodstream infections (CLABSIs) in our sister institutions in three countries including Brazil, Lebanon, and Japan. The 20 patients who received M-EDTA-EtOH lock therapy were compared to 24 control patients who had their CVCs removed and a new CVC inserted. Results : Both groups had comparable clinical characteristics. In the lock therapy group, 95% of the patients had microbiological eradication within 96 h after starting lock therapy versus 83% of the patients in the control group ( p = .36). In the lock group, the CVC was salvaged and retained for a median of 21 days (range 7–51) from the onset of bacteremia. Conclusion : Our study suggests that M-EDTA-EtOH lock therapy may be an effective intervention to salvage long-term CVCs in the setting of CLABSI/CRBSI and hemodialysis cancer patients with limited vascular access.